Identification of the Molecular Determinants Involved in Antimicrobial Activity of Pseudodesmin A, a Cyclic Lipopeptide From the Viscosin Group - De Vleeschouwer, Matthias; Van Kersavond, Tim; Verleysen, Yentl; Sinnaeve, Davy; Coenye, Tom; Martins, José C.; Madder, Annemieke (Frontiers in Microbiology, 2020)
Cyclic lipo(depsi)peptides (CLiPs) from Pseudomonas constitute a class of natural products involved in a broad range of biological functions for their producers. They also display interesting antimicrobial potential including activity against Gram-positive bacteria. Literature has indicated that these compounds can induce membrane permeabilization, possibly through pore-formation, leading to the general view that the cellular membrane constitutes the primary target in their mode of action. In support of this view, we previously demonstrated that the enantiomer of pseudodesmin A, a member of the viscosin group of CLiPs, shows identical activity against a test panel of six Gram-positive bacterial strains. Here, a previously developed total organic synthesis route is used and partly adapted to generate 20 novel pseudodesmin A analogs in an effort to derive links between molecular constitution, structure and activity. From these, the importance of a macrocycle closed by an ester bond as well as a critical length of β-OH fatty acid chain capping the N-terminus is conclusively demonstrated, providing further evidence for the importance of peptide-membrane interactions in the mode of action. Moreover, an alanine scan is used to unearth the contribution of specific amino acid residues to biological activity. Subsequent interpretation in terms of a structural model describing the location and orientation of pseudodesmin A in a membrane environment, allows first insight in the peptide-membrane interactions involved. The biological screening also identified residue positions that appear less sensitive to conservative modifications, allowing the introduction of a non-perturbing tryptophan residue which will pave the way toward biophysical studies using fluorescence spectroscopy.